Introducing Financial Management Information Systems in Developing Countries - Khemani, Pokar; Diamond, Jack. (Washington, D.C. : International Monetary Fund, 2005)
In the past decade, developing countries (DCs) have been encouraged to reform their public expenditure management systems and have increasingly embarked on major projects to computerize their government operations. Most popular among these have been projects to computerize government accounting and payment operations, by introducing government financial management information systems (FMISs). This paper investigates the reason for almost universal failure to implement and sustain FMISs in DCs. It starts with a review of the "received wisdom" in implementing these projects, and then analyzes problems in its application in the DC context to identify key factors to explain why FMIS projects have been so problematic. Based on the identified negative factors, suggestions for addressing them are offered in the hope of improving success rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet